2012
DOI: 10.4324/9780203113301
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of the European Social Model

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Our conclusions echo those of Whyman et al (2012) (based on literature which substantially overlaps with those we have cited above) when they write that 'there are a large number of studies which have found little or no significant impact arising from labour market deregulation' (p. 229).…”
Section: Do More 'Flexible' Labour Markets Lead To Better Economic Pesupporting
confidence: 79%
See 2 more Smart Citations
“…Our conclusions echo those of Whyman et al (2012) (based on literature which substantially overlaps with those we have cited above) when they write that 'there are a large number of studies which have found little or no significant impact arising from labour market deregulation' (p. 229).…”
Section: Do More 'Flexible' Labour Markets Lead To Better Economic Pesupporting
confidence: 79%
“…The key question which is to be addressed is how the ideas associated with the term European Social Model relate to the Economics and Monetary Union and the policies being advocated there and to the more general policy approaches of the European Union. As suggested in the quote from Whyman et al (2012) above, and becomes evident in the proposals on a 'fiscal compact', the policy drive is much more in the direction which may be described as neo-liberal, deregulation of labour markets and the advocacy of 'flexible labour markets'.…”
Section: Labour Market Institutions and Unemploymentmentioning
confidence: 94%
See 1 more Smart Citation
“…The idea of the self-regulating market is deeply ingrained in the recent austerity measures that further consolidated the neoliberal edifice (Whyman, Baimbridge, and Mullen 2012). Not only does the new treaty constrain the fiscal autonomy of the member states by requiring ex ante reporting and approval of their budgets (Treaty on Stability, Coordination and Governance in the Economic and Monetary Union 2012, Art.…”
Section: Extension Of the Neoliberal Creedmentioning
confidence: 99%
“…Also, the agreement that was supposed to remove borders within the EU (the Schengen Agreement, which Britain never joined), is currently suspended in many places because of the enormous pressure put on it by the movement of millions of refugees and other undocumented migrants across the EU member states’ territories during 2015 and parts of 2016. Also, what has been called the European Social Model, which has guided the idea of progressive economic, social, and employment policies in Europe, aiming to balance economic interests against social ones, is under severe pressure (Barbier, Rogowski, and Colomb ; Dølvik and Martin ; Vaughan‐Whitehead ; Whyman, Baimbridge, and Mullen ). Overall, it seems like the forces pulling things apart are becoming stronger than those that are pulling them together.…”
mentioning
confidence: 99%